Effect of Calcium Chloride and Trisodium Phosphate Fortification on Low Fat Buffalo Milk Cheeses - Perveen, R.; Butt, M.S.; Elahi, U.; Babur, M.N. (Indonesian Journal of Agricultural Research, 2024)
Cheese is a dairy product that is highly preferred by consumers. Cheese is a delectable and nutritious food item. Enhancing the quality of cheese necessitates innovation in cheese processing. The objective of the study was to determine the impact of calcium chloride and trisodium phosphate on the physical, chemical, microbiological, and rheological characteristics (namely firmness) of low-fat buffalo milk cheeses. This study had a fully randomized design, consisting of nine treatments and three replications. The cottage cheese, mozzarella, and cheddar were treated with varying quantities of calcium chloride and trisodium phosphate (10, 20, and 30 mM) and then stored for a period of 30 days. The cheeses supplemented with salt exhibited a noteworthy (pâ‰¤0.05) rise in pH, total nitrogen (TN), non-casein nitrogen (NCN), and non-protein nitrogen (NPN) for nearly all treatments. However, a subsequent decline was noted after storage. Similarly, the hardness (N) significantly improved (from 330.33 to 454) among treatments and reduced (from 427 to 276.33) after 30 days of storage, with a p-value of â‰¤0.05. In addition, the total plate count (TPC) and total viable count (TVC) showed an upward trend during the ripening phase. In conclusion, it was observed that the physicochemical, rheological, and microbiological quality characteristics of cheeses can be effectively regulated with appropriate mineral fortification.